Penanaman Modal Asing Di Ibu Kota Nusantara Melalui Skema Kerja Sama Pemerintah Dengan Badan Usaha - Rakhmani, Riki Taufik (Jurnal Hukum & Pembangunan, 2023)
One of the sources of funding for the development of Ibu Kota Nusantara is through the Public-Private Partnership (PPP) scheme. From the private sector's perspective, the PPP scheme provides access, particularly for foreign investors, to participate in providing infrastructure for the public's benefit. In order to attract foreign investors to participate in PPP for Ibu Kota Nusantara, the government can provide support, including transaction preparation and implementation facilities, feasibility support, tax incentives, government guarantees, and/or the use of state-owned assets. Guarantee for infrastructure provision through PPP is given against infrastructure risks caused by factors determined in the Minister of Finance Regulation. This article analyzes how foreign investment is implemented through the PPP scheme for infrastructure provision in the Ibu Kota Nusantara, as well as the protection provided to investors through government guarantees.